Development of a live attenuated vaccine against fowl adenovirus by mutating fiber gene using crispr –CAS9 technology - Salisu, Ahmed (2020)
Inclusion body hepatitis (IBH) is a commonly distributed poultry disease that has a huge economic impact on the poultry industry worldwide. Clinical finding is associated with bird age between 3 to 6 weeks old and is economically important due to significantly high mortality rates in young broiler birds that may reach up to 50%. Epidemiological studies demonstrated that all 12 serotypes of Fowl adenovirus are associated with the IBH where serotype-8b is a major concern due to highly pathogenic in chickens. The first IBH outbreaks due to FAdV serotype-8b was reported in Malaysia in 2005, since then the disease has been reported in several states of Malaysia involving major poultry producing areas. Vaccination against FAdV is not a common practice in Malaysia and a suitable vaccine against the disease is unavailable. Therefore, the need for the development of a safe and effective vaccine against IBH disease that can improve the health of poultry is highly important. The main objective of this study was to develop a live attenuated vaccine against FAdV by mutating its fiber gene using CRISPR-Cas9 technology. The Malaysian FAdV isolate (UPMT27) was propagated in specific pathogen free (SPF) chicken embryonated eggs and chicken embryonated liver (CEL) cells. Classical IBH lesions such as thickening and cloudy of the chorioallantoic membrane (CAM) were observed. The embryos show pale, petechial haemorrhages, multifocal area necrosis, swollen and yellowish liver, and formation of hydropericardium after eight days post inoculation (dpi). Cytopathic effect (CPE) of rounding, clumping, and detachment of the cells in CEL were observed at 72 hpi. Virus identification was successfully amplified by polymerase chain reaction (PCR) using FAdV specific primers of both fiber and hexon genes with an expected length of 882 bp and 2900 bp respectively. Nucleotide sequences of the fiber and the hexon genes was performed and phylogenetic tree was constructed. Phylogenetic analysis confirmed that the UPMT27 belongs to FAdV group E of serotype-8b. The result shows the UPMT27 had a high nucleotide identity (99%) with the previous Malaysian isolates (UPM1137E5; UPM1137E10 and UPM04217; UPM1137CEL10 for fiber and hexon respectively). Both fiber and hexon sequences were submitted to Genbank and the accession number was given as MT233531 and MT233532 respectively. The fiber gene of UPMT27 was successfully mutated and amino acid substitution was observed in the shaft region at position 179 (Tyrosine-Aspartate). The mutated virus (cfUPMT27) was subsequently rescued in the SPF chicken embryonated eggs. Pathogenicity study of the cfUPMT27 in SPF chicken embryonated eggs showed a predominant delayed pattern of mortality. Interestingly, the attenuated study showed that the mutated region of cfUPMT27 was genetically stable even after ten (10) consecutive passages. Pathogenicity study of the cfUPMT27 in CEL cell shows reduced in CPE activity. Morphological features of the transfected cells indicate that the cfUPMT27 was unable to localize at 48 hpi, while, it replicate and cause low CPE at 72 hours post inoculation (hpi). Meanwhile, the UPMT27 start to localize at 48 hrs and cause higher CPE at 72 hpi. Apoptosis assay demonstrated that the apoptotic rates in CEL cells infected with UPMT27 were significantly higher than those infected with cfUPMT27 at p<0.01. Interestingly, histopathological examination indicates that the cfUPMT27 caused less pathological damage to the liver tissue with the few concentration of the necrotizing lesion in the tubular cell. Meanwhile, the UPMT27 caused basophilic intranuclear inclusion surrounded with unaffected fibroblast in CELs. The viral copy number (VCN) (> log109) observed was significantly higher at 72 hpi in the UPMT27 infected cells compared with the cfUPMT27 with a significant reduction (3.6 x 10 1 and 4.2 x 102 copies ) at 24 and 48 hrs post-infection respectively. Pathogenicity and immunogenicity study of the cfUPMT27 was conducted in SPF chickens. Clinical appearance of the cfUPMT27 infected chickens is normal with no clinical signs observed throughout the trial. The chickens body and liver weight was significantly increased in all the three groups subcutaneous route (A), oral route (B), and control (C) from day 0, 7, and 21 dpi (p< 0.05) with highest mean number of body and liver weight in the chickens inoculated subcutaneously. No antibody was detected in group C throughout the trial. Surprisingly, antibodies against FAdV was detected at 7 dpi with the highest titre recorded at 21 dpi regardless of the route of inoculations; subcutaneous (A) and oral (B ) with 1568 ± 890.4 and 1265 ± 318.9 antibody titer respectively. Pathogenicity and immunogenicity evaluation demonstrated that the cfUPMT27 was safe and exhibited a good immune response in SPF chickens. Therefore, it was concluded that the CRISPR- based mutated FAdV (cfUPMT27) might be suggested as a potential vaccine in preventing the spread of FAdV serotype-8b in the poultry industry.